Making all Things New: the Laity as Transfigurers of the World - Crescio, Anthony (Gregorianum, 2021)
The Second Vatican Council resulted in significant developments in multiple areas of the study of theology, including ecclesiology, the theology of the laity, and moral theology. Moral theology has experienced a renewal in virtue and exemplarist ethics, yet generally continues to operate in isolation from ecclesiology and sacramental theology. In this essay, the work of Johann Adam Möhler is drawn from to articulate an ethics of virtue rooted in ecclesiology and the Church’s liturgical celebration, which is then used to discuss Christian exemplarity through the laity’s baptismalparticipation in the threefold office of Christ as priest, prophet and king.